2017 IEEE 56th Annual Conference on Decision and Control (CDC) 2017
DOI: 10.1109/cdc.2017.8263685
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing motion safety by identifying safety-critical passageways

Abstract: Abstract-Safety is the most important aspect of systems which have to perform collision-free motions in dynamic environments. Formal verification methods, such as reachability analysis, are capable of guaranteeing safety for a given model and given assumptions (e. g. bounded velocity and acceleration). However, certain assumptions can be violated by dynamic obstacles during the execution of the verified motion plan, exposing the system to potential collisions. To compensate for the invalidated verification, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…This paper formally defines and computes invariably safe sets, which are regions in which vehicles are able to remain safe for an infinite time horizon. This concretizes our previous work [23] for a lane-based setting, which considers arbitrary traffic scenarios. In contrast to computationally expensive approaches (cf.…”
Section: B Contributionsupporting
confidence: 82%
“…This paper formally defines and computes invariably safe sets, which are regions in which vehicles are able to remain safe for an infinite time horizon. This concretizes our previous work [23] for a lane-based setting, which considers arbitrary traffic scenarios. In contrast to computationally expensive approaches (cf.…”
Section: B Contributionsupporting
confidence: 82%
“…Since the mean values of all violations are only slightly above the initial values, the initial parameterization seems reasonable, but can be adjusted to user preferences. To reduce the influence of violated constraints on the safety of motion plans, we refer to [11]. Legal safety can be ensured despite constraint violations by planning fail-safe trajectories [15] and switching to a reactive mode for collision mitigation in case of inevitable collisions.…”
Section: Online Experiments On Public Roadsmentioning
confidence: 99%
“…In [8], we have shown that this does not result in overly conservative behaviors for the ego vehicle. Our proposed method has several applications for autonomous vehicles and driver assistance systems: a) Safe states: Based on the predicted occupancies, we can determine the maximum drivable area [9], the maximum Time-To-React [10], and the Point of No Return [11]. By additionally considering the predicted velocity, we can compute safe states for the ego vehicle, e. g., to maintain a safe distance to other vehicles [12].…”
Section: Introductionmentioning
confidence: 99%
“…Motion planning under uncertainties so far has been addressed through classical approaches [1,4,30,37,38], set-based methods [17,25,27,28], Markov Decision Processes (MDP) [9,34], and communication based approaches [33]. None of these works, however, accounts for the possibility of having an unreliable environmental model.…”
Section: Related Workmentioning
confidence: 99%